Theoretical Foundations For The Development Of Professional Training Of Future Engineers On The Basis Of Digital Technologies (Eurasian Journal of Learning and Academic Teaching, 2024)
This article aims to set the priorities for the development of the educational process based on the use of digital technologies in the higher education system of the Republic, the analysis of their capabilities, digital technologies in the field of education and in what form they were introduced.